AIE-active shape-persistent macrocycles for the efficient discrimination of toluene. (October 2020) - Yang, Linghui; Xu, Xiao; Yu, Wei; Li, Xianying; Zhang, Dengqing
Abstract: Efficient discrimination of toluene from volatile organic compounds is of great significance in the field of environmental protection. Herein, the novel AIE-active shape-persistent macrocycles (SPMs) were successfully synthesized by incorporating the propeller-shaped tetraphenylethylene (TPE) moieties into the framework. The macrocycle M1 displayed unique toluene-dependent fluorescence emission behavior, an emission peaking at 508 nm was observed in the absence of toluene, while first decreasing and then increasing fluorescence intensity along with blue-shift emission was witnessed with increasingly addition of toluene, accompanied by a visually discernible green-to-blue fluorescence color change. Furthermore, tunable visible-light emission including white-light was successfully achieved by the macrocycle M1 and rhodamine B two-component molecular system under toluene stimuli. The present system provided an efficient approach for discriminating toluene from volatile organic compounds. Graphical abstract: The novel AIE-active shape-persistent macrocycle M1 showed an emission peaking at 508 nm in the absence of toluene, while first decreasing and then increasing fluorescence intensity along with blue-shift emission was witnessed with increasingly addition of toluene, accompanied by a visually discernible green-to-blue fluorescence color change. Image 1 Highlights: The novel AIE-active shape-persistent macrocycles were synthesized. The macrocycle M1 can distinguish toluene from volatile organic compounds. A tunable multicolour fluorescence emission including white-light was achieved under toluene stimuli.